2017
DOI: 10.1093/cdj/bsx054
|View full text |Cite
|
Sign up to set email alerts
|

The art of bonding: informational capital in Dutch green urban citizens’ initiatives

Abstract: Today’s western society is characterized by a transition towards self-organization by citizens in communities. Increasingly, societal problems are addressed by groups of citizens who take action to find concrete solutions. A second feature of western society is that it is an information society in which information and communication play a key role. In this paper, we analyse how these two societal trends come together at the community level. Applying a relational and contingent perspective to how green urban c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
3
0
2
Order By: Relevance
“…Van Dam et al [9], however, found that information about the environment and relevant actors has a great effect on how an initiative meaningfully positions itself. Both formal and informal communication should function as antennae for exploring and mapping the environment and adjusting an organisation at the right time and in the right way in order to function optimally in realising its ambitions and at the same time build constructive relations [35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Van Dam et al [9], however, found that information about the environment and relevant actors has a great effect on how an initiative meaningfully positions itself. Both formal and informal communication should function as antennae for exploring and mapping the environment and adjusting an organisation at the right time and in the right way in order to function optimally in realising its ambitions and at the same time build constructive relations [35].…”
Section: Discussionmentioning
confidence: 99%
“…Demands and impacts of climate change, biodiversity loss, food production systems, energy transition, and flood-risk protection are putting our landscape under pressure [1,2]. Concurrently, there is a proliferation of self-organised citizen initiatives in support of improving the quality of the living environment [3][4][5][6][7][8][9][10]. The involvement of citizens in policy development and implementation is not new as it reflects a broader societal and scientific trend over the last twenty years, which is known as the transformation from government to governance [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…De doelgroepen in de sociale woningbouw geven geen prioriteit aan lokale groen-/gezondheidsprojecten in private en publieke ruimten en slagen er niet in hun bijdrage langjarig te leveren. Dit in tegenstelling tot wijken met andere sociaaleconomische klassen, waar wel succesvolle buurtinitiatieven plaatsvinden (Van Dam et al, 2017). Er is in armere buurten dus sturing en trekkerschap van andere actoren dan de bewoners nodig om projecten van de grond te tillen en te continueren.…”
Section: Mogelijkheden Voor Zelfbeheer En Participatie Door Bewonersunclassified
“…Sociaal kapitaal is zowel belangrijk voor de relaties binnen een organisatie als voor de relaties van een stakeholder met andere stakeholders, beiden kunnen bepalend zijn voor de invloed van een stakeholder (Hassink et al, 2016;van Dam et al, 2017). Sociaal kapitaal binnen een organisatie zorgt ervoor dat de organisatie een hecht netwerk is.…”
Section: Tellingenunclassified